Inheritance of seed weight and growth habit in 10 intercross chickpea (Cicer arietinum) nested association mapping populations. (17th November 2022) - Lakmes, Abdulkarim; Jhar, Abdullah; Penmetsa, R. Varma; Wei, Wenbin; Brennan, Adrian C.; Kahriman, Abdullah
Abstract: Objective of investigation: Chickpea is a major global food legume for which seed weight and plant growth habit are important yield and harvestability components for plant breeding. This study tested seed weight and plant growth habit inheritance and identified quantitative trait loci (QTL). Experimental material: A 10 nested association mapping (NAM) populations of chickpea were created from crosses between 'Gokce', a cultivar and wild crop relative accessions of Cicer reticulatum and Cicer echinospermum . Families were then developed to the F2:4 generation. Method of investigation: A 10 families were grown at the Field Experiment Station, Harran University near Şanlıurfa, Turkey during 2019. Data collection: A 100‐seed weight and prostrate or erect growth habit was scored in the field. Two families were genotyped for 60 single‐nucleotide polymorphisms (SNP). Result and conclusions: A 100‐seed weight showed polygenic control, and three QTLs were found. Growth habit was controlled by one or two QTLs. The two traits were significantly correlated for five populations. The crop wild relatives of chickpea contain variations at novel loci affecting seed weight compared to the literature. Abstract : The quantitative genetics of the important yield‐related traits of 100‐seed weight and erect or prostrate growth habit across 10 F2:4 nested association mapping (NAM) families of chickpea derived from crosses between a cultivar and wild crop relative accessions were studied. The results reveal variation in inheritance of both the continuous seed‐weight trait and the binary scored growth‐habit trait across families. These traits are associated in five of the mapping families, with implications for breeding from these materials. Quantitative trait locus (QTL) analysis of these traits in two of the mapping families was used to identify overlapping and distinct genomic regions associated significantly with each trait in each family. These QTLs reinforce previous findings in the literature and also contribute novel QTLs. The study contributes to understanding natural genetic variation and potential hybridizing value of wild crop relatives affecting yield‐associated traits of chickpea.